2022
DOI: 10.3389/fmed.2022.780475
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Face-Down Positioning and Adjustable Positioning After Pars Plana Vitrectomy for Macular Hole Retinal Detachment in High Myopia

Abstract: PurposeTo compare the anatomical and functional outcomes of macular hole retinal detachment (MHRD) in high myopia after pars plana vitrectomy (PPV) with face-down positioning and adjustable positioning.MethodsFifty-three eyes from 53 patients with MHRD were analyzed in this study. All patients received PPV with silicon oil for tamponade and then subdivided into 2 groups: 28 were included in a face-down positioning group and 25 were included in the adjustable positioning group. Patients were followed up for at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Gradually, some studies have reported the e cacy of postoperative positioning which did not require face-down positioning after vitrectomy for RRD 1-4, 10,11 . Our team has also achieved high success rates with adjustable positioning in treatment for RRD 12 and macular hole retinal detachment 13 . Based on these studies, we compared adjustable and free postoperative positioning after PPV for RRD to demonstrate the safety and effectiveness of free positioning.…”
Section: Introductionmentioning
confidence: 91%
“…Gradually, some studies have reported the e cacy of postoperative positioning which did not require face-down positioning after vitrectomy for RRD 1-4, 10,11 . Our team has also achieved high success rates with adjustable positioning in treatment for RRD 12 and macular hole retinal detachment 13 . Based on these studies, we compared adjustable and free postoperative positioning after PPV for RRD to demonstrate the safety and effectiveness of free positioning.…”
Section: Introductionmentioning
confidence: 91%
“…Our team has also achieved high success rates in treatment for RRD 12 and macular hole retinal detachment through patients' postoperative adjustable positioning. 13 In this study, we compared the safety and efficiency between adjustable and free postoperative positioning after PPV for RRD.…”
Section: Introductionmentioning
confidence: 99%
“…The long axis reduces the extension of the retina, resulting in the relative shortening of the retina and subsequent retinal splitting and detachment. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Possible mechanisms of HMMHRD include vitreoretinal traction caused by epiretinal membrane, residual vitreous cortex, inner limiting membrane (ILM) and retinal vascular system,9 which makes the vertical and tangential traction generated by the epiretinal membrane and ILM10 11 and further weakens the adhesion between retinal neuroepithelial layer and retinal pigment epithelium (RPE). The long axis reduces the extension of the retina, resulting in the relative shortening of the retina and subsequent retinal splitting and detachment 12…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation